2020
DOI: 10.1176/appi.neuropsych.20050111
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Related Growth: Building a More Resilient Brain

Abstract: FIGURE 3. An individual's ability to dismiss unwanted memories when they intrude into conscious awareness is an important aspect of healthy emotion regulation (16,17). This capacity is experimentally assessed by pairing items to be remembered with reminder cues and comparing results when participants are instructed to recall (Think) or instructed to not recall (NoThink) the paired items when cued. In healthy individuals, successful suppression of an intrusive memory weakens the memory trace (as indexed by decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 92 publications
3
15
0
1
Order By: Relevance
“…Relationships with other variables seems to evidence the scale validity. As expected ( Casellas et al, 2017 ; Lelorain et al, 2010 ; Linley & Joseph, 2004 ; Ochoa et al, 2019 ; Ord et al, 2020 ; Park, 2009 ; Park et al, 1996 ), a positive and significant association between SRG and positive affect and PPLC. Also, in line with literature ( Carver et al, 2009 ; Casellas et al, 2017 ; Holmaat et al, 2017 ; Lelorain et al, 2010 ; Marziliano et al, 2020 ; Ochoa et al, 2019 ), revealed no correlation, or very weak, between SRG and distress levels and negative affect.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Relationships with other variables seems to evidence the scale validity. As expected ( Casellas et al, 2017 ; Lelorain et al, 2010 ; Linley & Joseph, 2004 ; Ochoa et al, 2019 ; Ord et al, 2020 ; Park, 2009 ; Park et al, 1996 ), a positive and significant association between SRG and positive affect and PPLC. Also, in line with literature ( Carver et al, 2009 ; Casellas et al, 2017 ; Holmaat et al, 2017 ; Lelorain et al, 2010 ; Marziliano et al, 2020 ; Ochoa et al, 2019 ), revealed no correlation, or very weak, between SRG and distress levels and negative affect.…”
Section: Discussionsupporting
confidence: 79%
“…Studies show that approximately 40% of the cancer patients had a psychiatric disorder ( Derogatis et al, 1983 ; Mitchell et al, 2011 ; Reilly et al, 2013 ). However, for its nature, cancer can be simultaneously conceptualized as a major chronic stressor that can be a seismic event, threatening balance, and an end of life awareness trigger, and an event with the potential to capitalize the imminent ability of human beings to self-actualize and grow in a suffering circumstance ( Casellas et al, 2017 ; Cordova et al, 2017 ; Marziliano et al, 2020 ; Ord et al, 2020 ; Rzeszutek et al, 2020 ; Tremolada et al, 2018 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…. However, compelling research suggests that stress is not always a negative influence and that people, including children and adolescents, can grow and thrive as a result of times of stress (Ord et al, 2020;Vaughn et al, 2009;Waters, Allen et al, 2021).…”
mentioning
confidence: 99%
“…However, stress‐induced immune enhancement can also be negative/harmful if it exacerbates pathological immune responses that mediate pro‐inflammatory, allergic, or autoimmune responses (DiSabato et al, 2020). Considering coping outcomes, it is possible to distinguish whether the presence of stress promotes problem‐solving, brings about growth (Ord et al, 2020), or brings about negative effects and stress‐related disorders (Wu et al, 2019).…”
Section: How Can We Distinguish Between “Good Stress” and “Bad Stress”?mentioning
confidence: 99%